Extraventricular Lesions Demonstrated by Gastric Photofluorographic Study - OSHIBA, SABURO; IWABUCHI, JINJYU; MOCHIZUKI, FUKUJI; YAMAGATA, SHOICHI; SUGAWARA, NOBUYUKI; HISAMICHI, SHIGERU; SATO, KATSUYA; HADORI, SHIGEAKI; WATANABE, SHIGENORI (The Tohoku Journal of Experimental Medicine, 1976)
In a mass survey for diseases of the stomach with photofluorography, lesions other than those of the stomach were studied in 85, 040 subjects. Gastric lesions were detected in 2.17%, while other lesions were found in 1.97%, giving an approximately similar ratio. Duodenal lesions were found most frequently and in 1.47%, followed by intraabdominal calcification in 0.44%. Among duodenal lesions, duodenal ulcer was seen in 0.14%, and duodenal diverticulum in 0.34%. Among diseases with abdominal calcifications, calcification of lymph nodes was found most frequently and in 0.24%, followed by cholelithiasis in 0.085% and urolithiasis in 0.004%. Lower esophageal lesions were found in 0.05%, in which esophageal diverticulum was the most frequent and found in 0.034%.